P01.148 Intra-tumor heterogeneity analysis of low-grade gliomas. A POLA Network study. (19th September 2018) - Alentorn, A; Labreche, K; Dehais, C; Carpentier, C; Ducray, F; Mokhtari, K; Figarella-Branger, D; Sanson, M; Delattre, J; Idbaih, A; ,
Abstract: Background: Low-grade gliomas (LGG) are divided into three histo-molecular groups: i) IDHwt, ii) IDHmut and 1p19q intact and iii) 1p19q co-deleted with IDH1 mutation. The current classification has improved the clinical stratification and its reproducibility. However, LGGs are still associated with an important degree of clinical heterogeneity.We sough to analyze the genomic and genetic heterogeneity by re-analyzing next-generation sequencing data of two different cohorts of LGG to dissect the potential role of clonal architecture on the clinical evolution of LGG. Material and Methods: We have re-analyzed whole-exome sequencing (WES) using LGG TCGA dataset and a cohort of 40 LGG analyzed by WES from the POLA Network. We have obtained the clonal architecture, the mutation burden, the number of clones, the clonal and subclonal distribution of genetic and genomic alterations and the distribution of the somatic signatures. In addition, we have also analyzed 5 1p19q co-deleted samples at different timepoints to further dissect the clonal evolution of this entity. Results: As expected, the mutation burden of LGG is low (median somatic mutation per sample 34). Surprisingly, the number the subclones was higher in the 1p19q co-deleted subgroup.LGG were enriched in somatic signatures associated with hydrolytic deamination of methylated CpG and with deficiency of mismatch repair. Interestingly, only within 1p19q co-deleted gliomas, the number of subclones, the mutant-allele tumor heterogeneity (MATH) score and the signature associated with hydrolytic deamination of methylated CpGwere associated with poorer outcome in univariate analysis. Finally, only the enrichment of the mutational signature associated with hydrolytic deamination of methylated CpG had prognostic impact in 1p19q co-deleted LGG in Cox multivariate analysis afteradjusting by age, mutational clones number, MATH score and loss of CDKN2A loss. Conclusion: The clonal architecture of LGG may provide additional clinical relevant data within 1p19q co-deleted tumors. The enrichment of a somatic signature associated with hydrolytic deamination of methylated CpG is independently associated with poor overall survival.